Genome-wide characterization and expression analysis of MADS-box transcription factor gene family in Perilla frutescens - Liang, Mengjing; Du, Zhongyang; Yang, Ze; Luo, Tao; Ji, Chunli; Cui, Hongli; Li, Runzhi (Frontiers in Plant Science, 2024)
MADS-box transcription factors are widely involved in the regulation of plant growth, developmental processes, and response to abiotic stresses. Perilla frutescens, a versatile plant, is not only used for food and medicine but also serves as an economical oil crop. However, the MADS-box transcription factor family in P. frutescens is still largely unexplored. In this study, a total of 93 PfMADS genes were identified in P. frutescens genome. These genes, including 37 Type I and 56 Type II members, were randomly distributed across 20 chromosomes and 2 scaffold regions. Type II PfMADS proteins were found to contain a greater number of motifs, indicating more complex structures and diverse functions. Expression analysis revealed that most PfMADS genes (more than 76 members) exhibited widely expression model in almost all tissues. The further analysis indicated that there was strong correlation between some MIKC C -type PfMADS genes and key genes involved in lipid synthesis and flavonoid metabolism, which implied that these PfMADS genes might play important regulatory role in the above two pathways. It was further verified that PfMADS47 can effectively mediate the regulation of lipid synthesis in Chlamydomonas reinhardtii transformants. Using cis-acting element analysis and qRT-PCR technology, the potential functions of six MIKC C -type PfMADS genes in response to abiotic stresses, especially cold and drought, were studied. Altogether, this study is the first genome-wide analysis of PfMADS. This result further supports functional and evolutionary studies of PfMADS gene family and serves as a benchmark for related P. frutescens breeding studies.